2019
DOI: 10.3390/nano9121692
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Zinc Oxide Nanoflower Photocatalyst from Sea Buckthorn Fruit for Degradation of Industrial Dyes in Wastewater Treatment

Abstract: Green synthesis of ZnO nanoparticles has attracted research attention as a sustainable method of avoiding the destructive effect of chemicals. We synthesized a flower-shaped zinc oxide (ZnO) nanoflower (NF) from sea buckthorn fruit (SBT) by co-precipitation and characterized it using X-ray powder diffraction (XRD), X-ray photo electronic microscopy (XPS), photoluminescence (PL), field emission transmission electron microscopy (FE-TEM), and Fourier-transform infrared (FT-IR) spectroscopy. The ability of the ZnO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…Efforts are made to find an ideal dye removal method able to efficiently remove a large amount of dye in a short time, without generating further pollution by producing more hazardous by-products. To this end, the using of green synthesized metallic nanoparticles as efficient catalysts for the reduction of organic dyes has been largely explored [26][27][28]. The unique physical, chemical and electronic properties of metal nanoparticles recommend these nanomaterials as good catalysts, suitable for the reductive degradation of organic dyes, being an efficient alternative to conventional methods used for the removal of dye contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts are made to find an ideal dye removal method able to efficiently remove a large amount of dye in a short time, without generating further pollution by producing more hazardous by-products. To this end, the using of green synthesized metallic nanoparticles as efficient catalysts for the reduction of organic dyes has been largely explored [26][27][28]. The unique physical, chemical and electronic properties of metal nanoparticles recommend these nanomaterials as good catalysts, suitable for the reductive degradation of organic dyes, being an efficient alternative to conventional methods used for the removal of dye contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, wastewaters containing this type of dyes were highlighted as one of the most important threatening factors in environmental and public health [2,5]. Different studies have reported that there are several methods for removing dyes from textile wastewaters, including the application of photodecomposition [6], electrolysis [7,8], adsorption [9][10][11][12][13][14][15][16][17][18], oxidation [19], biodegradation [20], combined sonochemical and adsorption [21], coagulation-flocculation [22,23], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional (physical, biological, and chemical) wastewater (WW) treatment methods are costly, inefficient, complex, and produce secondary pollution [1][2][3]. Recently, advanced oxidation processes (AOPs) have been investigated due to the use of hydroxyl radicals (HO • ) formation, which exhibits strong oxidation capacity (E 0 = 2.76 V) [4], for example, homogeneous and heterogeneous Fenton [5,6], photo-Fenton, ozonation [7], hydrogen peroxide with ozone [8], hydrogen peroxide with UV [9], titanium dioxide/UV [10], zinc oxide/UV [11], and so forth.…”
Section: Introductionmentioning
confidence: 99%